Effect of probiotic consumption on immune response in athletes: A meta-analysis - Tavakoly, R.; Hadi, A.; Rafie, N.; Talaei, B.; Marx, W.; Arab, A. (International Journal of Sports Medicine, 2021)
The possible effect of probiotic interventions on immunological markers in athletes is inconclusive. Therefore, to synthesize and quantitatively analyze the existing evidence on this topic, systematic literature searches of online databases PubMed, Scopus, Cochrane Library, and ISI Web of Sciences was carried out up to February 2021 to find all randomized controlled trials (RCTs) concerning the immunological effects of probiotics in athletes. In the random-effects model, weighted mean difference (WMD) and 95% confidence interval (CI) explained the net effect. The authors assessed the likelihood of publication bias via Egger`s and Begg`s statistics. A total of 13 RCTs (836 participants) were retrieved. Probiotic consumption reduced lymphocyte T cytotoxic count significantly (WMD=-0.08 cells×109/L; 95% CI: -0.15 to -0.01; p=0.022) with evidence of moderate heterogeneity (I 2=59.1%, p=0.044) and monocyte count when intervention duration was = 4 weeks (WMD=-0.08 cells×109/L; 95% CI: -0.16 to -0.001; I 2=0.0%). Furthermore, leukocyte count was significantly elevated (WMD=0.48 cells×109/L; 95% CI: 0.02 to 0.93; I 2=0.0%) when multi-strain probiotics were used. Probiotic supplements may improve immunological markers, including lymphocyte T cytotoxic, monocyte, and leukocyte in athletes. Further randomized controlled trials using diverse strains of probiotics and consistent outcome measures are necessary to allow for evidence-based recommendations.